2015
DOI: 10.1186/s13613-015-0083-7
|View full text |Cite
|
Sign up to set email alerts
|

Automatic versus manual changeovers of norepinephrine infusion pumps in critically ill adults: a prospective controlled study

Abstract: BackgroundNorepinephrine is a key drug for treating shock but has a short half-life that requires continuous intravenous administration to maintain the constant plasma concentration needed to obtain a stable blood pressure. The small volume of the syringes used in power infusion pumps requires frequent changeovers, which can lead to norepinephrine flow interruptions responsible for hemodynamic instability. Changeovers from the nearly empty to the full syringe can be performed manually using the quick change te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 25 publications
1
8
0
1
Order By: Relevance
“…This result agrees with the few studies published on this topic in which the frequency of haemodynamic incidents related to vasoactive infusion pump changeovers varied from 5 to 38 % [ 2 7 , 10 , 11 ]. Obviously, the frequency of these incidents depends on the definition of CNIP-induced haemodynamic instability, which is not consensual [ 2 7 , 10 , 11 ]. We chose to define haemodynamic instability as a relative change in MAP rather than an absolute change in MAP.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…This result agrees with the few studies published on this topic in which the frequency of haemodynamic incidents related to vasoactive infusion pump changeovers varied from 5 to 38 % [ 2 7 , 10 , 11 ]. Obviously, the frequency of these incidents depends on the definition of CNIP-induced haemodynamic instability, which is not consensual [ 2 7 , 10 , 11 ]. We chose to define haemodynamic instability as a relative change in MAP rather than an absolute change in MAP.…”
Section: Discussionsupporting
confidence: 91%
“…low flow rates, entrapped air in the perfusion line, vertical displacements of syringe pumps) [ 2 , 12 14 ]. Above all, we used the safest available method to perform CNIP [ 5 , 7 , 8 ]. Indeed, both recent basic evidence and clinical evidence have suggested that the automation of a CNIP method without overlapping the perfusions (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations